2007
DOI: 10.1016/j.jnucmat.2007.01.110
|View full text |Cite
|
Sign up to set email alerts
|

Deuterium retention in rhenium-doped tungsten

Abstract: Structure changes (filling of voids in material) was found to take place both at annealing and low-energy deuterium irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0
2

Year Published

2012
2012
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 10 publications
1
30
0
2
Order By: Relevance
“…On one hand, both the differences in tungsten materials (i.e., preparation, structure, impurity content, pre-implantation history, etc.) and different analysis techniques for trapped D measurement (such as nuclear reaction analysis (NRA) and thermal desorption spectroscopy (TDS)) could essentially affect the experimental results of D retention in W [7,9,[11][12][13][14][15]. On the other hand, several approximations introduced in the model would also cause deviations, that is, excluding the formations of V n and D m V n ; ðn > 1Þ clusters and neglecting the adsorption of D by ion-induced dislocation loops.…”
Section: Model Validationmentioning
confidence: 99%
See 3 more Smart Citations
“…On one hand, both the differences in tungsten materials (i.e., preparation, structure, impurity content, pre-implantation history, etc.) and different analysis techniques for trapped D measurement (such as nuclear reaction analysis (NRA) and thermal desorption spectroscopy (TDS)) could essentially affect the experimental results of D retention in W [7,9,[11][12][13][14][15]. On the other hand, several approximations introduced in the model would also cause deviations, that is, excluding the formations of V n and D m V n ; ðn > 1Þ clusters and neglecting the adsorption of D by ion-induced dislocation loops.…”
Section: Model Validationmentioning
confidence: 99%
“…Therefore, series of experimental and theoretical researches on D retention in W have been carried out by considering different ion energies, fluxes and fluences as well as irradiation temperatures in the past few years [2,5,[7][8][9][10][11][12][13][14][15][16][17]. The retention of D in W exposed to D ion beams and D plasmas have been investigated extensively for a wild range of experimental conditions as well as several analysis techniques [7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Golubeva et al [5] reported that after irradiation with 200 eV D ions at 300 K, deuterium retention in W-Re alloys was higher that than in polycrystalline W. In a study by Tyburska-Püschel and Alimov [6], W and W-3%Re samples were initially damaged by irradiation with 20 MeV W ions to simulate n-induced displacement damage and then were exposed to low-energy (76 eV/ion), high flux (10 22 D/m 2 s) D plasma at various temperatures. Results obtained showed that at exposure temperatures above 450 K the concentration of deuterium trapped at W-ion-induced defects in W-3%Re alloy is significantly lower than that in pure W. However, there are no results on hydrogen retention in undamaged W-Re materials exposed to high flux hydrogen plasmas.…”
Section: Introductionmentioning
confidence: 99%